The association between rs12885713 polymorphism in CALM1 and risk of osteoarthritis: A meta-analysis of case–control studies. Issue 36 (September 2018) - Shi, Jia; Gao, Shu-tao; Lv, Zheng-tao; Sheng, Wei-bin; Kang, Hao
Abstract: Objective: The single nucleotide polymorphism (SNP) rs12885713 of calmodulin 1 gene ( CALM1 ) has been reported to involve in the etiology of osteoarthritis (OA) in several association studies with limited sample size and conflicting results. The purpose of the present systematic review and meta-analysis was to evaluate and synthesize the currently available data on the correlation between rs12885713 and OA susceptibility. Methods: Six electronic databases including PubMed, EMBASE, ISI Web of Science, CNETRAL, CNKI, and Wanfang were systematically retrieved to identify relevant observational articles published before October 2017. Summary odds ratios (ORs) and corresponding 95% confidence intervals (95% CIs) were calculated to indicate the association between CALM1 polymorphism and OA. Risk of bias was assessed through the Newcastle-Ottawa Scale. Predetermined subgroups and sensitivity analyses were performed using the RevMan 5.3 software. Publication bias was evaluated by Egger and Begg tests. Results: Overall, 5 case–control studies involving 2183 OA patients 2654 healthy control subjects satisfied the meta-analysis. Recessive model was confirmed to be the best-matching genetic model (TT + TC versus CC). The pooled outcomes indicated that rs12885713 SNP was not significantly associated with OA vulnerability (OR 1.11, 95% CI 0.97, 1.27; P  = .12). When stratified by different genders, OA sites, and population descents respectively, still non-significant associations were found. Conclusion: Based on the findings of our present study, the rs12885713 polymorphism of CALM1 did not appear to be associated with OA predisposition.